Measurement of soil radon concentration in Balikesir and examination of its effects on health - Celen, Yonca Yahsi; Gunay, Osman; Oncul, Sule; Narin, Baris (ELSEVIER, 2023)
Most of the natural radiation originates from radon, approximately 55%. This radiation occurs because of the radioactive decay of natural uranium found in rocks, soil and water. Because radon is in gaseous form, it can easily leak into living spaces and accumulate. Inhalation of radon and radon decay products is a significant health risk factor. Considering the high mortality rate of lung cancer in our country, inhalation of high radon concentrations has been associated with the risk of lung cancer. Accurate measurement of radon levels is especially important for dose assessment of radon exposure. In this study, it was aimed to determine the natural radon concentrations in Balikesir province and districts using the active method by soil measurement using the AlphaGUARD portable radon detector, and to perform radiological risk analyzes by determining the radon levels of the region covering Balikesir Province by measuring the natural radiation emitted from the soil. As a result of the measurements, the lowest radon concentration amount was measured in Akcay district of Balikesir province and its average value is 17.65 +/- 2.71 kBq/m3. The humidity in the environment is 72.34%, the average pressure is 1013.61 hPa and the average temperature is 33.02 degrees C. The highest radon concentration amount was measured in Havran district of Balikesir province and its average value is 66.71 +/- 2.52 kBq/m3. The humidity in the environment is 58.61%, the average pressure is 1007.91 hPa and the average temperature is 31.80 degrees C.
Keywords: Cancer; Radon; Natural radioactivity; Soil; AlphaGUARD; INDOOR RADON; RADIOACTIVITY LEVELS; RADIONUCLIDES; RADIATION; PROVINCE; SAMPLES; WATER; GAS; Science & Technology - Other Topics; Radiology, Nuclear Medicine & Medical Imaging